HUBUNGAN KEHARMONISAN KELUARGA DENGAN PENYESUAIAN DIRI PESERTA DIDIK DI KELAS IX SMP NEGERI 1 SUNGAI RUMBAI KABUPATEN DHARMASRAYA - Suryana, Desi - (Bimbingan dan Konseling, 2014)
Family as the smallest social group in society, have an infortant role in the formations of self adjustment in children. This research aims the describe: (1) harmony family, (2) adaptability learner, (3) test, wether there is a significant relationship between the harmony of families with adaptability learners. This research is a descriptive quantitative research corelational. The population of this research is class IX student of SMP Negeri 1 Sungai Rumbai Dharmasraya Regerency school year 2014/2015 and research samples taken using simple random sampling techniques that 60 bo people. Instrument of the research is questionnaire, for the data analysis using percentage and corelation technique. Research findings show that of 34,5% learner feel the harmony of family is harmonious, 35,9% adaptabilty learners belongs to already good relations while the harmony family of conformity obtained r count of 0,413 and r table of 0,254 the significance level 0,05, so it can be inferred that there is a significant relationship between the harmony of the family with the learners adaptability.